An electrochemical-TUNEL method for sensitive detection of apoptotic cells. Issue 2 (28th October 2015) - Liu, Shanhu; Zhang, Ziyi; Zhou, Shiwei; Jiang, Li-Ping; Zhu, Jun-Jie
Abstract : An electrochemical-TUNEL method based on the fabrication of a CNT@PDA–FA three dimensional bio-interface was developed for cytosensors. By being coupled with a QD-based nanoprobe and electrochemical analysis, the sensor exhibited attractive performance in the detection of apoptotic cells. Abstract : An electrochemical-TUNEL method was developed for a cell sensor. A 3-D bio-interface based on CNT@PDA–FA was employed in the cytosensor, which significantly improved the cell capture. By coupling with a QD-based nanoprobe and electrochemical stripping analysis, the cytosensor exhibited attractive performance for detection of apoptotic cells.